A Study of Transnational and Transformation Leadership Styles and Factors Affect The Leadership Style - Deveshwar, Aarti; Aneja, Indu (International Journal of Business, Economics and Management, 2014)
Current Global Corporative World provides the opportunity to the organizations to interact with various nations across the geographical limits. These interactions grant the cultural and value variations among the nations which recognized as the biggest challenge in front of the corporative managers. Suitability of an organization depends on the Effective leadership style in the complex competitive world. An Effective and Efficient Leadership style is the best tool to face these kinds of challenges. The paper focuses on the most popular Leadership style used by the international organizations in the current scenario. The study represents the picture of the existing literature on Transactional and Transformational Leadership styles and as well as on the cross-cultural dimensions model given by Greet Hofstede. The objectives of the paper (a) Comparative study of Transactional and Transformational Leadership Style and (b) Determine the cultural factors affect the leadership style.